2022
DOI: 10.1186/s12903-022-02479-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of artificial saliva on the cleaning force of interdental rubber picks: an in-vitro comparison

Abstract: Background The familiar aids for interdental cleaning such as dental floss or interdental brushes (IDB) are often associated with difficult handling or an increased potential for trauma. Interdental picks (IRP), which have no metal core and silicone flaps instead of nylon brushes, offer the alternative. However, in-vitro studies found a lower cleaning effectiveness combined with higher forces for cleaning compared with conventional IDBs. The aim of this in-vitro study was to measure the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Regarding the influence of lubrification, one laboratory study assessed experimentally the cleaning forces (ECF) with rubber sticks with and without artificial saliva also in a 3D‐printed interdental space model resembling human teeth with three different morphologies (isosceles triangle, convex, and concave) 23 . This study found that artificial saliva reduced the cleaning force by half and therefore potentially allowed for using even larger brush diameters.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the influence of lubrification, one laboratory study assessed experimentally the cleaning forces (ECF) with rubber sticks with and without artificial saliva also in a 3D‐printed interdental space model resembling human teeth with three different morphologies (isosceles triangle, convex, and concave) 23 . This study found that artificial saliva reduced the cleaning force by half and therefore potentially allowed for using even larger brush diameters.…”
Section: Discussionmentioning
confidence: 99%